2015
DOI: 10.1517/14712598.2015.1051528
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells: an overview of their potential in cell-based therapy

Abstract: HUC-MSCs seem to be an optimal choice for stem cell-based therapy. However, before the cells translate from basic to clinical research, some problems still remain to be solved: i) building regulatory guidelines as well as an efficient and safe manufacturing procedure; ii) establishing donor's genetic testing and long-term closely monitoring system; iii) conducting further clinical trials to determine the optimum and standard dosage, time, route, frequency and many other technical issues of HUC-MSCs transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
118
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(133 citation statements)
references
References 89 publications
(54 reference statements)
2
118
0
1
Order By: Relevance
“…Therefore, EnSCs are a potential alternative way to treat ovarian cancer and other diseases. However, there are still some challenges like other cell-based therapies535455. Firstly, the fate and long-term efficiency of transplanted EnSCs are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EnSCs are a potential alternative way to treat ovarian cancer and other diseases. However, there are still some challenges like other cell-based therapies535455. Firstly, the fate and long-term efficiency of transplanted EnSCs are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, previous studies have indicated that a large number of MSCs exist in umbilical cord tissues, known as human umbilical cord mesenchymal stem cells (huMSCs) 5 . Clinical application of huMSCs is extensive, because not only do huMSCs express all the biological characteristics of bone marrow MSCs but they also exhibit good proliferation, differentiation potential and low immunogenicity 6 . Therefore, huMSCs are ideal seed cells in tissue engineering 7 .…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that bone marrow derived-mesenchymal stem cells (BM-MSCs) loaded on collagen scaffolds improved regeneration of fresh wounds of the uterine wall via the secretion of fibroblast growth factor 2 (FGF2), insulin-like growth factor 1(IGF1) and vascular endothelial growth factor (VEGF) [22]. As a primitive population of MSCs between fetal and adult MSCs, umbilical cord-derived mesenchymal stem cells (UC-MSCs) have shown their prominent advantages in abundant supply, painless collection and high proliferative potential [2328]. Accumulating evidence has shown that UC-MSCs facilitate the repair of bones, skin and peripheral nerves [2931] and improve the function of organs following injury including the brain, kidneys and liver [3234].…”
Section: Introductionmentioning
confidence: 99%